(untitled) (Mustansiria Dental Journal, 2018)
This in vitro study evaluated and compared the apical sealing ability of two obturation techniques and two type of instrumentation. A total of 120 teeth were collected randomly divided into two groups 60 roots prepared using hand protaper, other 60 roots prepared using rotary protaper .Each group was subdivided randomly into two obturation groups of 30 roots for each; in group A- obtura II was used ,and in group B-thermafill (TF) was used. Then the samples in all groups left for a week at room temperature. After coronal sealing, all surfaces of the root covered with three layer of nail polish except the apical 2mm, then each sample immersed in 10% black Indian ink dye for 72 hours .After that the samples rinsed and nail polish removed .then samples cleared & decalcified.Data had been collected from independent examiners and statistically analyzed using student t-test. The stereomicroscopic results showed that there was highly significant difference between hand and rotary instrumentation, with in favor of rotary instrumentation technique. Concerning the obturation techniques, Thermafill showed best apical sealing followed by Obtura II; however, the differences were not significant.